«Item canevarius habet». Un quaternus chartarum duecentesco del comune di Bormio (1237-1287) - Pezzola, Rita (Scrineum, 2013)
Written documents and records were increasing in number at the time of the medieval communes, together with a peculiar success of more and more effective ways in order to use and to keep them. This can be said for Bormio as well (Sondrio - Italy), especially from the first half to the end of the thirteenth century. This edition of the thirteenth-century quaternus chartarum is particularly precious and significant. Actually it lets us better understand that period, analyzing the organization of written documents (there are transonti documents from 1237 to 1287). Research accompanying the edition reveals that the practice of recording is a clear evidence of the level of maturation reached by the municipal administration.